Dexamethasone in Treatment of Comorbid SARS-CoV-2 Patients Aged over 50 Years with Lung Injury over 50 % - O. Yu. Zolnikova; R. V. Maslennikov; V. T. Ivashkin; N. L. Dzhakhaya; O. Yu. Kiseleva; N. D. Potskhverashvili; S. A. Shorokhova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. An efficacy assessment of steroid therapy in SARS-CoV-2 patients aged over 50 years with lung damage over 50 % (grade 3–4).Materials and methods. A retrospective study of 158 SARS-CoV-2 patients hospitalised in April—June 2020 was conducted under the inclusion criteria: age over 50 years, chest computed tomography (CT) for COVID-19-asso-ciated pneumonia, C-reactive protein (CRP) >50 mg/L, anticoagulant therapy, no contraindications to steroids, no biologic therapy. Cohort 1 patients (n = 96) received dexamethasone 4–12 mg/day, cohort 2 (n = 62) — a standard non-dexamethasone therapy.Results. Dexamethasone treatment associated with a significant alleviation of COVID-19-associated pneumonia in CT score (p = 0.001), reduced fibrinogen (p = 0.001), a trend to CRP reduction by day 8–10 and lower demand for oxygen therapy, including ventilatory support (p = 0.001). Mortality rate was 19.8 and 75.8 % in cohorts 1 and 2, respectively (p = 0.001).Conclusion. Dexamethasone therapy 4–12 mg/day in SARS-CoV-2 patients aged 50+ years with grade 3–4 CT changes receiving LMWH from start of hospitalisation significantly improved CT scores and reduced mortality.